TANGGAPAN PENGGUNA PELAYANAN KESEHATAN RAWAT JALAN DI PUSKESMAS BAURENO BOJONEGORO - Zakariya, Zakariya; Gunawan, Kunto Inggit; Mataji, Mataji (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
The implementation of good and professional public services seems to have becomesomething urgent for the community. Competition between companies or service providers isgetting tougher and making the public more critical of the quality of services requiringgovernment institutions to always improve the quality of their services. Baureno Health Centerin Bojonegoro Regency is a public service institution that carries out the function of healthservices for the community. Therefore, each institution has an obligation to carry out periodicmeasurements about people's perceptions of service. This study wants to examine in depthanalyzing the health services of the Baureno Health Center in Bojonegoro Regency. Themethods are: service procedures, service requirements, clarity of service officers, discipline ofservice personnel, service personnel personnel, service staff capability, service speed , servicejustice, courtesy and hospitality of service personnel, fairness of service costs, suitability ofservice costs, timeliness of service, convenience of environment, environmental security,complaint handling, infrastructure and facilities. The results of the preparation for theCommunity Satisfaction Index at Baureno Health Center in Bojonegoro Regency in November December2018haveaverygoodcategory,thatis,theIKMweightedaveragevalueis3.285orIKMconversion is 82.14. The community considered overall outpatient services, which wereprovided by the Baureno Health Center in Bojonegoro Regency to be very good.Keyword: Public Respon - Street Health Service